Physiological responses of resistance training in increasing brain-derived neurotrophic factor levels: a systematic review - danypramunoputra dany; Devi Arianti; Melya Rossa; Dimas Aji Prayitno; Fransiskalina Erfarenata; Junian Cahyanto Wibawa (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Cognitive function decline is a hallmark of dementia, a progressive neurological disease. One neurotrophin that is crucial to neuroplasticity, cognition, and mental health is brain-derived neurotrophic factor (BDNF). Exercise has currently been shown to be an effective non-pharmacological treatment for enhancing overall health. It is still unknown whether weight exercise raises BDNF levels.